Otimizaçâo das condições de preparação de eletrodos à base de carbono cerâmico utilizando-se planejamento fatorial - Skeika,Tatiane (2010)
Different parameters of carbon ceramic electrodes (CCE) preparation, such as type of precursor, carbon material, catalyst amount, among others, significantly influence the morphological properties and consequently their electrochemical responses. This paper describes a 2³ factorial design (2 factors and 3 levels with central point replicates), which the factors analyzed were catalyst amount (HCl 12 mol L-1), graphite/precursor ratio, and precursor type (TEOS - tetraethoxysilane and MTMOS - methyltrimetoxysilane). The design resulted in a significant third order interaction for peak current values (Ipa) and a second order interaction for potential difference (ΔE), between thefactors studied, which could not be observed when using an univariated study.